Innovative system for delivery of low temperature district heating - Ianakiev, Anton Ivanov; Cui, Jia Michelle; Garbett, Steve; Filer, Andrew (International Journal of Sustainable Energy Planning and Management, 2017)
An innovative Low Temperature District Heating (LTDH) local network is developed in Nottingham, supported by REMOURBAN project, part of the H2020 Smart City and Community Lighthouse scheme. It was proposed that a branch emanating from the return pipe of the of the existing district heating system in Nottingham would be created to use low temperature heating for the first time in UK. The development is aimed to extract wasted (unused) heat from existing district heating system and make it more efficient and profitable. Four maisonette blocks of 94 low-raised flats, at Nottingham demo site of the REMOURBAN project will be connected to this new LTDH system. The scheme will provide a primary supply of heat and hot water at approximately 50oC to 60oC. Innovated solutions have been put forward to overcome certain barriers, such as legionella related risks and peak loads during extreme heating seasons and occasional maintenance.